Implementation of PPH Article 21 Private Persons at Kukutio Puskesmas, Kolaka Regency, Southeast Sulawesi Province - Baso Mukhaimin Asmar (JEKAMI Journal of Accounting, 2021)
This study aims to determine whether the application of Income Tax Article 21 at the Kukutio Health Center is in accordance with the calculation of Income Tax Article 21 according to the tax law. This type of research is descriptive quantitative. The source of data used in this research is secondary data. Secondary data data obtained from the Kukutio Public Health Center. The results of this study indicate that there is a difference in the calculation of PPh article 21 that has been carried out by the Kukutio Health Center with the calculation of PPh article 21 according to the customs law.